Preparation and characterization of Poly-3-hydroxybutrate/Poly(butylene-adipate-terephthalate) stearate-modified Zn3AI-layered double hydroxide nanocomposites - Pak, Yen Leng (2014)
The present research aims at studying the influence of layered double hydroxide (LDH) on the properties of Poly(3-hydroxybutyrate)/Poly(butylene adipate-co-terephthalate),(PHB/PBAT). LDH is a synthetic clay which can be easily prepared through coprecipitation method. However, it is incompatible with organic material due to its hydrophilic nature. The LDH was modified via ion exchange method using organic surfactant, sodium stearate to increase its hydrophobicity and compatibility with organic materials. The characterization of modified sterarate LDH was carried out by X-ray Diffraction (XRD), Fourier Transfrom Infrared Spectroscopy (FTIR) and Thermogravimetric analysis (TGA). XRD and FTIR results indicated LDH was successfully modified through the ion exchange method. XRD showed that the basal spacing of pristine LDH increased with the formation of modified LDH. The PHB/PBAT blend was successfully prepared by solvent casting method. FTIR spectra revealed that the blends involved only physical interaction as there were no new functional groups or new bonding present. Tensile strength and modulus decreased as the PBAT contents increased due to elastic characteristic of PBAT. SEM micrograph of the PHB/PBAT clearly demonstrated a two phase morphology, which indicated the immiscibility of the component. For the result of PHB/PBAT blend, the onset temperature, the temperature at the Tmax of PHB and the Tmax of PBAT are found to decrease as compared to the pristine polymer. This indicated that the PHB/PBAT blend have an effect on the acceleration of thermal decomposition. Thus, the addition of PBAT to PHB in the weight ratio of 10% has decreased the thermal stability of virgin PHB. The PHB/PBAT nanocomposites were prepared by solvent casting technique. The expansion of the basal spacing of the modified LDH indicated the formation of intercalated types of nanocomposites which supported by the presence of diffraction peak in XRD diffractograms and TEM images. TEM images results revealed that the modified LDH layers are homogeneously distributed in the PHB/PBAT polymer blends matrix. Mechanical property of the nanocomposites with 2 wt% modified LDH content show 56% improvement in elongation at break compared to those of the blend. The significant enhancement in the elongation at break of the nanocomposites is due to the presence of modified LDH that act as a plasticizer.Furthermore, the thermogravimetric analysis showed the presence of modified stearate LDH resulting in significant improvement in thermal stability of The PHB/PBAT nanocomposites were prepared by solvent casting technique. The expansion of the basal spacing of the modified LDH indicated the formation of intercalated types of nanocomposites which supported by the presence of diffraction peak in XRD diffractograms and TEM images. TEM images results revealed that the modified LDH layers are homogeneously distributed in the PHB/PBAT polymer blends matrix. Mechanical property of the nanocomposites with 2 wt% modified LDH content show 56% improvement in elongation at break compared to those of the blend. Thesignificant enhancement in the elongation at break of the nanocomposites is due to the presence of modified LDH that act as a plasticizer. Furthermore, the thermogravimetric analysis showed the presence of modified stearateLDH resulting in significant improvement in thermal stability of nanocomposites,especially 2 wt% nanocomposite as compared to pristine polymer blend.nocomposites,especially 2 wt% nanocomposite as compared to pristine polymer blend.